KARAKTERISTIK KARBON AKTIF DARI KULIT BUAH MALAPARI (Pongamia pinnata L. Pierre) - Ibrahim; Djeni Hendra; Nur Adi Saputra; Eti Rohaeti (BRIN Publishing, 2022)
Vegetable oil production of malapari (Pongamia pinnata L. Pierre) fruit remains peels that haven't been utilized. Malaparifruit peel is potential for activated carbon. The purpose of this research is to use malapari fruit peel waste as raw material forproducing activated charcoal. Samples were carbonized at temperature of 400°C and continued activation with phosphoric acid2% and physical activation at temperature of 750°C by flowing steam for 60 minutes. The process resulted in the Optimumcondition. It yields 54% charcoal recovery, moisture content of 8.6%, volatile matter of 11.85%, ash content of 24.73%, fixedcarbon of 63.42%, benzene adsorptivity of 10.15%, metilene blue adsorptivity of 93.89 mg/g, iodine adsorptivity of 648.62mg/g, and specific surface area of 348.11 m2/g. Activated carbon in this study is below Indonesian standards, which is influencedby the activation retention time.